2003
DOI: 10.1021/jp021694w
|View full text |Cite
|
Sign up to set email alerts
|

Use of ab Initio Calculations toward the Rational Design of Room Temperature Ionic Liquids

Abstract: Ionic liquids are gaining substantial interest as alternative reaction media. Despite the overwhelming amount of evidence suggesting a relationship between their structure and melting point, there still remains the problem of selectively choosing a particular ionic pair that will produce a liquid at room temperature. Ionic liquids based on 1-alkyl-3-methylimidazolium halides have been investigated using ab initio calculations utilizing Gaussian 98 and the 6-31G* and 6-31+G* basis sets. The calculated interacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
333
2
5

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 358 publications
(362 citation statements)
references
References 23 publications
21
333
2
5
Order By: Relevance
“…According to the calculated minimum energy E e of the conformers, the GA was more stable than the AA conformer, but at 298.15 K the Gibbs energy of the AA conformer was 0.168 kJ mol À1 less than that of the GA conformer, indicating 52% of anti-anti vs. 48% of gauche-anti or almost equal amounts of the two conformers at equilibrium at room temperature [103]. A higher difference between the AA and GA energy was found in other calculations [131]. These results are consistent with the observation of both conformers being simultaneously present in the spectra of the [C 4 mim] þ cation liquids are given in Fig.…”
Section: Brief Introduction To Ab-initio Model Calculationsmentioning
confidence: 54%
See 2 more Smart Citations
“…According to the calculated minimum energy E e of the conformers, the GA was more stable than the AA conformer, but at 298.15 K the Gibbs energy of the AA conformer was 0.168 kJ mol À1 less than that of the GA conformer, indicating 52% of anti-anti vs. 48% of gauche-anti or almost equal amounts of the two conformers at equilibrium at room temperature [103]. A higher difference between the AA and GA energy was found in other calculations [131]. These results are consistent with the observation of both conformers being simultaneously present in the spectra of the [C 4 mim] þ cation liquids are given in Fig.…”
Section: Brief Introduction To Ab-initio Model Calculationsmentioning
confidence: 54%
“…The calculated interaction energy was found to increase in magnitude with decreasing alkyl chain length at the Hartree-Fock level, but no trend was found with increasing halide anionic radius. Linear trends between melting point and interaction energy were found to exist for the 1-butyl-3-methylimidazolium halide series as well as for the 1-alkyl-3-methylimidazolium iodide series [131]. …”
Section: Other Studies On [C N Mim]mentioning
confidence: 93%
See 1 more Smart Citation
“…As an example, the observed melting point change for ionic liquids with different anions was explained in terms of the change in the interaction energy and the relative position depending on the anion. 14,40 Many calculation studies found that the relative position of the anion with respect to the cation could change with the anion type 9,[14][15][16]20,21 and, in case of imidazolium-based ionic liquid, proposed that the interaction between the anion and H-C(2) is crucial in determining this structure. 15,18,19,40,41 The recent simulated IR spectrum in the 2800-3200 cm -1 range was shown to change with anion position.…”
Section: Discussionmentioning
confidence: 99%
“…12, 13 Calculations that followed suggested that the above cation conformation change would alter the position of the anion and change the interaction between the anion and the cation in 1-alkyl-3-methylimidazolium halide ionic liquids. [14][15][16] An important issue in the structure of an ionic liquid is the relative position between the anion and cation comprising the bulk liquid. In the study of a mixture of methyl-ethyl imidazolium chloride ([MEI][Cl]) and AlCl 3 molten salt, Dieter et al first proposed that Cl -interacts preferentially with the hydrogen attached to C(2), C(4), and C(5) of the imidazolium ring.…”
Section: Introductionmentioning
confidence: 99%